Screening and Resistance Response of Brinjal Rootstocks (Solanum melongena) against Root-knot Nematode, Meloidogyne incognita for Tomato Grafting (Indian Journal of Nematology, 2024)
The root-knot nematode (RKN-Meloidogyne incognita) is an important biotic stress in tomato affecting plant growth and crop yield worldwide, especially under protected cultivation. In the present study, 23 brinjal genotypes were screened for resistance against M. incognita under screen-house conditions for tomato grafting. After 40 days of inoculation, GU-BP1P24a (R-19) and GU-BP16 (R-20) genotypes were found highly resistant (RKI = 1), while GU-BP12a (R-6) was found resistant (RKI = 2). These three genotypes were further used as rootstocks for grafting in three commercial tomato scions (Hisar Arun, Pusa Rohini, and Arka Rakshak), which were showing high susceptibility to nematode infestation and, therefore, were grafted on resistant brinjal rootstocks. The most productive combination was scion Arka Rakshak when grafted onto GU-BP16 (R-20) rootstock; this increased yield by 16.1 per cent (364.9 q/ha) in comparison to non-grafted scion Arka Rakshak when grown in nematode sick plots. The rootstocks provided resistance to scions against RKN in the nematode-infested conditions and reduced the number of galls by 75.6 to 81.3 per cent, the number of egg masses by 64.4 to 79.0 per cent, and the final nematode count up to 54.8 per cent.